2018
DOI: 10.1186/s40463-018-0304-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of skull X-RAY to determine cochlear implant insertion depth

Abstract: BackgroundCochlear implant (CI) insertion depth can affect residual hearing preservation, tonotopic range coverage, and Mapping. Therefore, determining insertion depth has the potential to maximize CI performance. A post-op skull X-RAY is commonly used to assess insertion depth, however its effectiveness has not been well established. Our primary objective was to assess the accuracy of post-op skull X-RAYs to determine insertion depth, compared to CT as the gold standard. Secondary objectives were to compare e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A conventional CT may be more precise than plain radiographs, but multiple studies have shown that plain radiographs perform equally well in determining insertion depth and extracochlear electrodes, avoiding exposure to high-dose ionising radiation. [14][15][16] In our study, we endeavoured to address the inherent imprecision of plain radiographs by taking a higher threshold of 2 or more electrodes lateral to the approximate position of the round window to define extracochlear electrodes. With this definition, the prevalence of migration in our study cohort concurs with a previous report using CT to define EM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A conventional CT may be more precise than plain radiographs, but multiple studies have shown that plain radiographs perform equally well in determining insertion depth and extracochlear electrodes, avoiding exposure to high-dose ionising radiation. [14][15][16] In our study, we endeavoured to address the inherent imprecision of plain radiographs by taking a higher threshold of 2 or more electrodes lateral to the approximate position of the round window to define extracochlear electrodes. With this definition, the prevalence of migration in our study cohort concurs with a previous report using CT to define EM.…”
Section: Discussionmentioning
confidence: 99%
“…Cone beam computed tomography (CT) scan is often considered gold standard for determining EM, however, this modality is not routinely available, 13 and not at our centre during this period. A conventional CT may be more precise than plain radiographs, but multiple studies have shown that plain radiographs perform equally well in determining insertion depth and extracochlear electrodes, avoiding exposure to high‐dose ionising radiation 14–16 . In our study, we endeavoured to address the inherent imprecision of plain radiographs by taking a higher threshold of 2 or more electrodes lateral to the approximate position of the round window to define extracochlear electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative audiometric monitoring can often be performed while the surgeon is closing the surgical site to avoid prolonging the duration of anesthetic. Finally, an anterior-posterior skull X-ray can be performed to confirm appropriate positioning of the electrode within the cochlea, verifying the insertion depth and absence of kinking or tip rollover ( Fernandes et al., 2018 ); other X-ray views such as lateral or Stenver’s ( Shaul et al., 2020 ) could be performed depending on surgeon preference.…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…The accuracy of estimating electrode location using computer tomography (CT) images has been demonstrated in studies comparing measurements made radiographically to those determined on histologic review 24 , 25 . Studies comparing aDOI measurements obtained from CTs have also shown comparable accuracy to those obtained using conventional radiography 26 , 27 . Measurements of aDOI using radiographs have shown good reliability in vitro as well as in adult CI listeners 7,23,26 .…”
mentioning
confidence: 91%
“…24,25 Studies comparing aDOI measurements obtained from CTs have also shown comparable accuracy to those obtained using conventional radiography. 26,27 Measurements of aDOI using radiographs have shown good reliability in vitro as well as in adult CI listeners. 7,23,26 This has not been demonstrated in infants and young children, who may be more challenging to position for a cochlear view.…”
mentioning
confidence: 99%